If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2) + -2y = 2 Multiply 4 * 2 8 + -2y = 2 Solving 8 + -2y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -2y = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -2y = 2 + -8 -2y = 2 + -8 Combine like terms: 2 + -8 = -6 -2y = -6 Divide each side by '-2'. y = 3 Simplifying y = 3
| -3n(2n-9)=0 | | (2x+3)(x-2)+(8x-1)(x+1)=0 | | (2xy^6-y)dx+(2x)dy=0 | | 5y-6b(c)=7 | | 4y^2-y=3y-3 | | (m^-2p^2/2mp^3)^-3 | | -2x-7=-3x+3 | | 5x=(245/8) | | 4x=-2x+8 | | ma=-kx-FAcos(watA) | | 3x=(320/4) | | 6.1y-302=26.08 | | 2-18=z/-8 | | (.8)^t=1/8 | | 0.4+0.2x=0.2+x | | 7z=14-35 | | -3.5=-.5g | | 96=r^2+10r | | 2(7c+5)= | | 2x+2.3=7.7 | | -9(9x+9)=10(10x+10) | | 3(2x+5)=2(6x-3) | | ln(x-23)-In(5-x)=In(4)+In(x) | | y^2+12y=35 | | 25=5(x-3) | | 2(x+3)+4(x-2)=0 | | -3.6h=(-10.8) | | 5lgx=3 | | 2x-3=-7x+12 | | 8/32 | | 1-4y=-32 | | 4n+8n+5n-3= |